Fighting the Pandemic with "Shields": Successful COVID-19 Securitization and Mask Policy in Taiwan. (March 2023) - Chang, Chia-Chien; Yen, Wei-Ting; Liu, Li-Yin
Facemasks have been proven an effective non-pharmaceutical measure against coronavirus disease-19. Against the backdrop of global mask shortages, Taiwan distinguished herself from other countries in that Taiwan took a whole-of-nation approach to masks and mobilized the society quickly to become self-sufficient in masks. This paper argues that successful virus securitization as a threat to national security was what enabled Taiwan to effectively mobilize the private sector to carry out the state's will in ensuring adequate mask supply. Moreover, Taiwan securitized the virus more successfully than many other countries because the virus was connected to China, the nation's existing security threat.